Teaching language and literacy in Grade R: A focus on letters and sounds within a story-based programme - O'Carroll, Shelley (Wordworks, 2023)
The low early grade reading levels of South African children are well documented (Van Staden & Gustafsson, 2022). Recent PIRLS results highlight challenges with reading comprehension at Grade 4 level, but studies also show that many children are not acquiring alphabet knowledge earlier in their reading trajectory, and that these children are more likely to struggle with reading fluency and comprehension in later years (Wills, Ardington & Sebaeng, 2022). But why is learning about letters and the sounds they make proving to be such a difficult task for the majority of children in South Africa? When is the optimal time to be learning about letters and would it make a difference if alphabet knowledge had a stronger focus in Grade R? Local and international research is clear: letter–sound knowledge is critical for learning to read and write in an alphabetic language (Snow, Burns & Griffin, 1998; Castles, Rastle & Nation, 2018). What remains controversial is when and how best to support children to learn about letters and the sounds they make. Drawing on research and best practice for teaching young children, this paper highlights the key principles that underpinned the development of materials to teach letter–sound knowledge in Grade R. These materials were developed as part of a story-based Home Language programme for the Gauteng Grade R Language Improvement Project, a provincial teacher training programme targeting all Grade R teachers in public ordinary schools, special needs schools and registered ECD centres in Gauteng.
Further information about the project as well as creative commons licensed resources can be accessed here: https://www.jet.org.za/clearinghouse/projects/grade-r-maths-and-languageimprovement-project/resources or contact the developers at info@wordworks.org.za.
Keywords: Grade R; early literacy; letter-sound knowledge; teacher training; South Africa